Unusual Magnetic Behaviors and Electronic Configurations Driven by Diverse Co(II) or Mn(II) MOF Architectures - Bernini, Maria Celeste (2014)
Five novel metal organic frameworks were obtained by hydrosolvothermal reactions using the hexafluorisopropylidenebis(benzoic) acid (H2hfipbb) as linker and Co(II) or Mn(II) ions as connectors. [Co2(Hhfipbb)- (TEA)], compound 1 (TEA = triethanolamine trianion) with a threedimensional (3D) framework, and a tpu net; [Co1.5(hfipbb)2]·HN(CH2CH3)3 and [Co3(hfipbb)2]·2{HN(CH2CH3)3}, compounds 2 and 2-a, respectively, both with two-dimensional structure, sql topologies, and different layer packings. Compounds 3 and 4, having the general formula [M2(hfipbb)2]·C7H8, where M = Co (3) or Mn (4), have 3D frameworks with an sqc topology. A deep analysis of the magnetic measurements reveals different striking magnetic behaviors resulting from diverse secondary building unit and framework architectures. Compound 1 presents canted antiferromagnetic chains, compound 2 contains ferromagnetic linear trimeric clusters, and compound 3 exhibits ferromagnetic chains. For the three compounds, a 3D canted antiferromagnetic structure takes place at ∼8 K by means of weak magnetic interactions between the mentioned magnetic units. Such long-range magnetic order is precluded with the application of a high enough magnetic field. Compound 4 evidenced intrachain antiferromagnetic interactions.